ANALISIS PERBANDINGAN KINERJA KEUANGAN TERHADAP PENGELOLAAN ALOKASI DANA DESA TAHUN 2023-2024 (STUDI KASUS DESA MALUKA BAULIN DAN DESA RADEN KECAMATAN KURAU) - Ines Saraswati Machfiroh; Nor Rahma Rizka; Faisal Fadly Pulungan; Siti Ramadina (Realible Accounting Journal, 2026)
This research is motivated by the importance of transparent, efficient, and effective village financial management in order to improve the welfare of the village community. However, in practice, there are still variations in financial performance between villages in the management of Village Fund Allocation (ADD). This study aims to analyze and compare financial performance in the management of Village Fund Allocation (ADD) in Maluka Baulin Village and Raden Village, Kurau District, during 2023 to 2024. Proper management of ADD is an important indicator in improving the quality of public services, development, and empowerment of village communities. This study uses a quantitative approach with a comparative descriptive method. The data used is in the form of secondary data from the budget realization report of the two villages. The analysis was carried out through the calculation of four financial ratios, namely: effectiveness ratio, efficiency ratio, dependency ratio, and compatibility ratio. The results of the study show that there is a difference in the level of financial performance between the two villages. Maluka Baulin Village shows more efficient management and has a good level of spending compatibility, while Raden Village shows a consistently high level of effectiveness, but still has a considerable level of fiscal dependence on the central government. These findings are expected to be evaluation material in improving more optimal and sustainable village financial governance.